USING PHYSICAL AND PHYSIOLOGICAL TESTS AS AN INDICATOR OF PHYSICAL EFFICIENCY FOR YOUNG FOOTBALL PLAYERS - Md. Adnan Mohammed Shanawa (Proximus Journal Publishing, 2025)
The research included five chapters. The first chapter contained the introduction and the importance of the research. The researcher addressed the importance of tests in the field of football. The focus was on physical tests, including strength endurance and speed endurance, as well as physiological tests, including pulse rate and what it represents as an important indicator and the relationship of these variables to physical efficiency and the possibility of predicting the percentage of contribution of these physical and physiological variables to the physical efficiency of young football players. The problem of the research lies in the fact that there is a weakness in the level of physical efficiency of young players. Therefore, the study came to identify the weaknesses, identify them, diagnose them, and give coaches the opportunity to stand on the real level of players and predict these results in the future. The aim of the research is to identify some physical and physiological variables of young football players and to identify the relationship of these physical and physiological variables to the physical efficiency of young football players. The research imposed a correlation between some physical and physiological variables and the physical efficiency of young football players. The research areas consisted of three areas: the human area
Keywords: Physical tests; Physiological tests; Strength endurance